The Influence of Occupational Safety Culture on Compliance With the use of Personal Protective Equipment (PPE) Among PT X Workers - Sri Wahyuni; Sri Sundari; Muhammad Irwandi Harahap; Klisa Putri Zahra; Nurliana Hasibuan; Tri Niswati Utami (Universitas Ibn Khaldun Bogor, 2026)
Personal Protective Equipment (PPE) is rarely used, or even never used, so it looks untouched. This indicates that workers have limited knowledge about the importance of reducing Occupational Safety and Health (OSH). Personal Protective Equipment (PPE) is equipment used by workers to protect their bodies from accidents or illnesses caused by work in the work environment. Many employes believe it's unnecessary to wear PPE; this is especially true for employes who wear standard clothing and feel comfortable at work. This research is a quantitative study using a survey (observational) method and a cross-sectional (analytical) approach. This research was conducted at a concrete company in one of Indonesia's regions, with a total sample size of 29 samples. Based on the results of hypothesis testing, it was found that safety culture has a positive and significant influence on PPE usage compliance. This means that the higher the safety culture, the higher the PPE usage compliance. Based on these findings, it can be concluded that if you want to increase PPE usage compliance, safety culture also needs to be improved.